Emergence of Anthrax Edema Toxin as a Master Manipulator of Macrophage and B Cell Functions - Gnade, Bryan T. (MDPI, 2010)
Anthrax edema toxin (ET), a powerful adenylyl cyclase, is an important virulence factor of Bacillus anthracis. Until recently, only a modest amount of research was performed to understand the role this toxin plays in the organism’s immune evasion strategy. A new wave of studies have begun to elucidate the effects this toxin has on a variety of host cells. While efforts have been made to illuminate the effect ET has on cells of the adaptive immune system, such as T cells, the greatest focus has been on cells of the innate immune system, particularly the macrophage. Here we discuss the immunoevasive activities that ET exerts on macrophages, as well as new research on the effects of this toxin on B cells.